(untitled) (Bangladesh Journal of Animal Science, 2019)
An experiment was conducted with Napier grass (NG) treated with Poultry droppings (PD) and rice straw and ensiled with molasses to increase the nutritional and preservation quality of Napier grass. Chopped Napier grass was preserved in plastic containers under airtight condition at room temperature based on the treatments T0 (0% PD), T1 (15% PD), T2 (30% PD) and T3 (45% PD) with 5% molasses and 20% rice straw as fresh basis in each treatment to investigate physical quality, chemical composition, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content at 0, 30, 45, 60 and 75 days. The physical quality (color, smell, and hardness) of Napier grass mixer were improved in Poultry droppings added treatments till 75 days of ensiling. The pH value was decreased (P<0.05) with the increasing of PD and ensiling time. The dry matter (DM), crude protein (CP) and ash were increased (P<0.05) and crude fiber (CF) was decreased (P<0.05) in all the treatments (T1, T2 and T3) compared to control one T0. The CP, DM and ash were increased (P<0.05) and CF and EE were decreased (P<0.05) after ensiling. The EE content was not signified (P>0.05) between T1 and T2. The CF content was decreased (P<0.05) with the increase of Poultry droppings and ensiling time. The organic matter digestibility (OMD) and metabolizable energy (ME) content were increased (P<0.05) with the PD level and ensiling time. Considering all the physical and chemical properties, among all the treatments, 30% and 45% PD are acceptable for preparing wastelage. Thus cost effective and environment friendly feed can be prepared. Bang. J. Anim. Sci. 2019. 48 (1): 48-56